F Formulasi dan Evaluasi Sediaan Lipbalm Ekstrak Umbi Bit Merah (Beta vulgaris L.) Sebagai Antioksidan - Yuli Yanti Sholehah; Siti Malahayati; Ali Rakhman Hakim (LPPM Universitas Sari Mulia, 2022)
Background: Lipbalm is a preparation commonly used for lips that useful as a moisturizer, decorative, and protect lips environmental influences, and prevents evaporation of the ephitelial cells of mucosa lips. Red beetroot is a ppurplish red plant that contains antioxidant betacyanin. Objective: Identify the formulation of the reed beetroot extract (Beta vulgaris L.) lipbalm based on evaluation results and identify the effect of various concentration of cera alba based on evaluation result. Methods: The research design use a experimental research with quasy experimental with one group post-test only which compare variation of concentration of cera alba to the lipbalm formulation of red beetroot extract (Beta vulgaris L.) as an antioxidant. Results: In the preparation of red beetroot extract (Beta vulgaris L.) lipbalm obtained 4 formulation where formulation I, II, III, and IV met the specifications for organoleptic, homogeinity, adhesion, dispersibility, and pH. Evaluation result of the formulation of lipbalm preparation of red beetroot extract (Beta vulgaris L.), variation in the concentration of cera alba affect the result of the physical and chemical evaluation. Conclusion: Preparation of red beetroot extract (Beta vulgaris L.) lipbalm where formulation I, II, III, and IV met the specifications for organoleptic, homogeinity, adhesion, dispersibility, and pH. The evaluation result of the lipbalm formulation of red beetroot extract (Beta vulgaris L.) theres an effect of variation in concentration of cera alba as base for physical and chemical evaluation. The optimal formulation is formula III. Keywords: Antioxydant, Cera alba, Lipbalm, Lips, Red beetroot